An experimental investigation of water tension on hydrophobic surface - Chan, Kim Hang. (2011)
Self-cleaning surfaces have received a great attention and are highly desirable as they have endless potential applications. This surface can be achieved through two approaches, either the use of a hydrophilic surface or a hydrophobic surface. With reference to Wenzel and Cassie and Baxter, hydrophobicity is determined by the high contact angle, surface tension and surface roughness. An ultra hydrophobic surface refers to a surface which has a water contact angle bigger than 150°. In order to achieve an ultra hydrophobic surface, we can either increase the surface tension of the substrate or increase the surface roughness without affecting the substrate. In this research, the student will be investigating the surface tension on hydrophobic surface. He will fabricate a hydrophobic coating on the glass slides via sol-gel method and alter the surface roughness with the use of aluminum oxide nanoparticles. Different size of aluminum oxide nanoparticles will be used, and the sizes are 10nm, 80nm and 150nm. The hydrophobicity will be determined by the contact angle of the water droplet on the glass slide and the surface roughness is determined by the use of atomic force microscope or the confocal imaging profiler.